2019
DOI: 10.1590/0037-8682-0505-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methodologies for detecting Trypanosoma cruzi parasites by microscopic observation of microhematocrit capillary tubes

Abstract: Introduction: The microscopic examination of microhematocrit tubes (mHCT) has been proposed as the gold standard for acute and congenital Chagas disease diagnosis. We compared different mHCT methodologies detecting T. cruzi parasites in the blood. Methods: The rotating method, water mount, and immersion oil methods were compared for their suitability, sensitivity, and specificity. Results: The rotating method was easier, faster, and more sensitive than the others with 100% specificity. Conclusions: The rotatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The black lines in the dots represent the median values of parasitemia levels. The color background is defined considering the limit of detection of microhematocrit, 0 to 40 parasite equivalents/mL (white), >40 to 500 parasite equivalents/mL (very light blue), >500 to 10,000 parasite equivalents/mL (light blue), and >10,000 parasite equivalents/mL (blue) ( 31 33 ). F , Friedman test value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The black lines in the dots represent the median values of parasitemia levels. The color background is defined considering the limit of detection of microhematocrit, 0 to 40 parasite equivalents/mL (white), >40 to 500 parasite equivalents/mL (very light blue), >500 to 10,000 parasite equivalents/mL (light blue), and >10,000 parasite equivalents/mL (blue) ( 31 33 ). F , Friedman test value.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no consensus on the values at which parasitemia is considered low or high ( 30 ). In our previous work, the degree-of-parasitemia ranges were determined considering the LOD of a microhematocrit test according to data from previous studies by Vera-Ku et al (LOD, 10,000 parasites/mL) ( 31 ) and Torrico et al (LOD, 40 parasites/mL) ( 32 ). In this study, we also added a complementary LOD (500 parasites/mL) according to data described previously by Feilij et al ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…For analysis, the categorical factor was infection (congenital infection, chronic infection), and the continuous responses were time to positivity and degree of parasitemia. Degree of parasitemia ranges were determined considering the limit of detection (LOD) of a microhematocrit test according to Vera-Ku et al (LOD, 10,000 par/ml) ( 33 ) and according to Torrico et al (LOD, 40 par/ml) ( 26 ). Par, parasites.…”
Section: Resultsmentioning
confidence: 99%
“…Although MHT is the fastest method to detect T. cruzi (less than 20 min), its sensitivity depends on the operator’s skills, the degree of parasitemia, and whether the sample is examined within 12 h after collection ( 13 , 26 , 33 ). Reports from some South American countries showed that MHT sensitivity was 34.2% in the first month of age ( 34 ), 76.1% up to 6 months of age ( 15 ), and 94% in 1 year of follow-up ( 14 ), whereas qPCR could detect up to 84.2% of infected infants before 1 month of age ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, BCM gives good results for , c, e, g, i, k, m) and methanol-fixed Giemsa-stained blood films (b, d, f, h, j, l, n) microfilariae and Trypanosoma species detection. The BCM has been known and extensively used in human medicine [45,47,48,75,76]. In veterinary medicine, it was mainly applied for examination of mammalian blood samples, with a focus on diagnostics of parasitic infections with zoonotic potential [47,52,53,[77][78][79].…”
Section: Discussionmentioning
confidence: 99%